USE OF THE STATE PROGRAM “FIRST STEP” IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (Scientific journal of the Fergana State University, 2024)
This article provides information on the current state of development of the preschool education system and the reforms being carried out in the field. In the process of child development, information about the use of the “First Step” state curriculum in pre-school educational institutions and its importance today has been highlighted. The implementation of the state program “First Step” in every preschool education organization acts as a factor that brings the reforms implemented in the field into a certain system today.